2013
DOI: 10.1002/ppap.201300098
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fibroblast Cell Proliferation and Migration Using Atmospheric N2 /Ar Micro-Plasma for the Stimulated Release of Fibroblast Growth Factor-7

Abstract: In situ assessment of cell functions on N2/Ar micro‐plasma exposed fibroblast cells is examined to better understand the effect of atmospheric low‐dose plasma treatment. The cells number increased threefolds for plasma exposure time of 5 or 10 s, followed by cell culture for 48 h. The cell coverage rate rose 20% for the same plasma exposure time, followed by cell culture for 6 or 12 h. 0.5% N2/Ar micro‐plasma exposure can particularly be used to achieve the stimulated release of FGF7 and subsequent enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 23 publications
(29 reference statements)
1
34
0
Order By: Relevance
“…Plasma application can be a double‐edged sword, as it may affect cellular function in different directions. On the one hand, plasma may stimulate proliferation of cells, as has been documented for endothelial cells, peripheral blood mononuclear cells and fibroblasts, while on the other hand, plasma has been shown to induce apoptosis in a number of different cell types . Earlier findings suggested induction of pro‐proliferative signals after short‐term plasma exposure to human HaCaT keratinocytes, as detected by phosphorylation of extracellular‐regulated kinase (ERK)1/2 signalling (mitogen‐activated protein kinase; MAPK), whereas prolonged plasma treatment caused phosphorylation of p38 and MEK1/2 signals, and hence led to enhanced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma application can be a double‐edged sword, as it may affect cellular function in different directions. On the one hand, plasma may stimulate proliferation of cells, as has been documented for endothelial cells, peripheral blood mononuclear cells and fibroblasts, while on the other hand, plasma has been shown to induce apoptosis in a number of different cell types . Earlier findings suggested induction of pro‐proliferative signals after short‐term plasma exposure to human HaCaT keratinocytes, as detected by phosphorylation of extracellular‐regulated kinase (ERK)1/2 signalling (mitogen‐activated protein kinase; MAPK), whereas prolonged plasma treatment caused phosphorylation of p38 and MEK1/2 signals, and hence led to enhanced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…. Several experimental in vitro studies could demonstrate a direct impact of CAP on cell proliferation and migration as well as on angiogenesis(68)(69)(70)(71)(72)(73)(74)(75)(76). The stimulating effect on skin tissue regeneration was confirmed in vivo 33: 1011-1026 (2019) Schematic of interactions between the kINPen plasma effluent with aqueous liquid.…”
mentioning
confidence: 97%
“…18,19 Numerous studies have shown a possible link between plasma-generated RONS in cell culture media to apoptosis, cell proliferation, migration, and angiogenesis. [20][21][22][23][24] A UV-Visible absorption spectroscopy (UVAS) procedure was developed to monitor the real-time changes in concentrations of RONS and aqueous oxygen [O 2 (aq)] in deionized (DI) water during plasma jet treatment. 25 This and follow-up studies have shown that although He and Ar plasma jets efficiently deliver RONS into DI water, at the same time these plasma jets also de-oxygenate DI water.…”
mentioning
confidence: 99%
“…Skin cells were chosen because of the intense interest in the plasma stimulation of skin cells to aid in the healing of chronic wounds. 23,[37][38][39][40][41] Cells were cultured in Dulbecco modified Eagle's medium (DMEM) supplemented with 10% (v/v) fetal bovine serum, 100 IU ml À1 penicillin, and 100 lg ml À1 streptomycin at 37 C under a humidified atmosphere of 5% CO 2 . A total of 5000 cells suspended in 200 ll of cell culture medium was added to 96well tissue culture polystyrene plates and incubated for 24 h prior to treatments.…”
mentioning
confidence: 99%